Serine-Phosphorylated STAT3 Promotes Tumorigenesis via Modulation of RNA Polymerase Transcriptional Activity - Balic, Jesse J; Garama, Daniel J; Saad, Mohamed I; Yu, Liang; West, Alison C; West, Alice J; Livis, Thaleia; Bhathal, Prithi S; Gough, Daniel J; Jenkins, Brendan J (Cancer research (Chicago, Ill.), 2019)
Deregulated activation of the latent oncogenic transcription factor STAT3 in many human epithelial malignancies, including gastric cancer, has invariably been associated with its canonical tyrosine phosphorylation and enhanced transcriptional activity. By contrast, serine phosphorylation (pS) of STAT3 can augment its nuclear transcriptional activity and promote essential mitochondrial functions, yet the role of pS-STAT3 among epithelial cancers is ill-defined. Here, we reveal that genetic ablation of pS-STAT3 in the spontaneous gastric cancer mouse model and human gastric cancer cell line xenografts abrogated tumor growth that coincided with reduced proliferative potential of the tumor epithelium. Microarray gene expression profiling demonstrated that the suppressed gastric tumorigenesis in pS-STAT3-deficient mice associated with reduced transcriptional activity of STAT3-regulated gene networks implicated in cell proliferation and migration, inflammation, and angiogenesis, but not mitochondrial function or metabolism. Notably, the protumorigenic activity of pS-STAT3 aligned with its capacity to primarily augment RNA polymerase II-mediated transcriptional elongation, but not initiation, of STAT3 target genes. Furthermore, by using a combinatorial and proteomics approach based on the rapid immunoprecipitation mass spectrometry of endogenous protein (RIME) assay, we identified RuvB-like AAA ATPase 1 (RUVBL1/Pontin) and enhancer of rudimentary homolog (ERH) as interacting partners of pS-STAT3 that are pivotal for its transcriptional activity on STAT3 target genes. Collectively, these findings uncover a hitherto unknown transcriptional role and obligate requirement for pS-STAT3 in gastric cancer that could be extrapolated to other STAT3-driven cancers. SIGNIFICANCE: These findings reveal a new transcriptional role and mandatory requirement for constitutive STAT3 serine phosphorylation in gastric cancer.